2019
DOI: 10.1038/s41598-019-51965-5
|View full text |Cite
|
Sign up to set email alerts
|

Early renal dysfunction and fibroblast growth factor-23 in patients with small vessel disease-related stroke

Abstract: Interactions between cerebral small vessel disease (CSVD) and renal dysfunction (RD) have been reported, but previous studies were mostly retrospective and limited to measurements of estimated glomerular filtration rate (eGFR). In this prospective, longitudinal study of patients with CSVD-related recent small subcortical infarcts (RSSI), we aimed at a comprehensive exploration of markers of early RD and their association with microvascular brain damage. We investigated 101 stroke patients (mean age: 60.2 ± 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Besides a thorough clinical neurological assessment and cerebrovascular workup (duplex sonography of extra- and intracranial brain-supplying arteries, echocardiography, and 24-h Holter ECG), patients underwent blood sampling and brain MRI at baseline and at 3 and 15 months after their index event. Detailed description of the study cohort has been reported elsewhere [ 8 , 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Besides a thorough clinical neurological assessment and cerebrovascular workup (duplex sonography of extra- and intracranial brain-supplying arteries, echocardiography, and 24-h Holter ECG), patients underwent blood sampling and brain MRI at baseline and at 3 and 15 months after their index event. Detailed description of the study cohort has been reported elsewhere [ 8 , 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…There are many studies about the relationship between kidney injury and the occurrence of IS [22][23][24][25][26]. Few scholars believe that only IS can induce kidney injury [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Few scholars believe that only IS can induce kidney injury [23,24]. Many scholars have con rmed that not only IS can induce kidney injury, but also kidney injury can induce IS [25][26][27]. The structure and function of the microvascular system of the brain are similar to that of the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our research shows that hypertensive patients with CKD, diabetes, stroke, or gout were associated with kidney function decline, which is consistent with previous studies. Diabetes mellitus, CKD, stroke, and gout are independent risk factors for renal disease [35,[44][45][46].…”
Section: Discussionmentioning
confidence: 99%